Combining CRISPR-Cas12a-Based Technology and Metagenomics Next Generation Sequencing: A New Paradigm for Rapid and Full-Scale Detection of Microbes in Infectious Diabetic Foot Samples - Chen, Yixin; Shi, Ya; Zhu, Weifen; You, Jiaxing; Yang, Jie; Xie, Yaping; Zhao, Hanxin; Li, Hongye; Fan, Shunwu; Li, Lin; Liu, Chao (Frontiers in Microbiology, 2021)
Introduction: Diabetic foot infections (DFIs) pose a huge challenge for clinicians. Staphylococcus aureus, including methicillin-resistant S. aureus (MRSA), is one of the most significant pathogens of DFI. Early pathogen identification will greatly benefit the diagnosis and treatment of the disease. However, existing diagnostic methods are not effective in early detection. Methods: We developed an assay that coupled loop-mediated isothermal amplification (LAMP) and clustered regularly interspaced short palindromic repeats (CRISPR) techniques to enable quick and specific detection of Staphylococcus aureus and differentiate MRSA in samples from patients with DFI. Furthermore, the results were compared using a reference culture, quantitative real-time polymerase chain reaction (qRT-PCR), and metagenomics next generation sequencing (mNGS). Results: The CRISPR-LAMP assay targeting nuc and mecA successfully detected S. aureus strains and differentiated MRSA. The limit of detection (LoD) of the real-time LAMP for nuc and mecA was 20 copies per microliter reaction in comparison to two copies per μL reaction for the qRT-PCR assay. The specificity of the LAMP-CRISPR assay for nuc was 100%, without cross-reactions with non-S. aureus strains. Evaluating assay performance with 18 samples from DFI patients showed that the assay had 94.4% agreement (17/18 samples) with clinical culture results. The results of mNGS for 8/18 samples were consistent with those of the reference culture and LAMP-CRISPR assay. Conclusion: The findings suggest that the LAMP-CRISPR assay could be promising for the point-of-care detection of S. aureus and the differentiation of MRSA in clinical samples. Furthermore, combining the LAMP-CRISPR assay and mNGS provides an advanced platform for molecular pathogen diagnosis of DFI.